Hexamethyldisilazane-iodine induced intramolecular dehydrative cyclization of diamides: a general access to natural and unnatural quinazolinones - Kshirsagar, Umesh A.; Mhaske, Santosh B.; N. P. Argade (Tetrahedron Letters, 2007)
A simple and efficient general approach to various quinazolinone scaffolds, including peptidomimetic examples, has been demonstrated by employing HMDS/I-2 for the intramolecular dehydrative cyclization of diamides. The protecting groups -Boc, -Fmoc and -Cbz tolerated the present reaction conditions and we did not observe any racemization. The present protocol has also been used as a key step for the efficient four-step syntheses of the naturally occurring quinazolinones, sclerotigenin, (-)-circumdatin-F and (-)-fumiquinazoline-F. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: diamides; HMDS/I-2; intramolecular dehydrative cyclizations; natural and unnatural quinazolinones; synthesis

Highly enantioselective synthesis of sitagliptin - Khopade, V. Kishor; Sen, Anirban; Birajdar, Rajkumar S.; Paulbudhe, Uday P.; Kavale, Dattatry S.; Shinde, Prashant S.; Mhaske, Santosh B.; Chikkali, Samir H. (Asian Journal of Organic Chemistry, 2020)
A highly enantioselective synthesis of sitagliptin, a potent DPP-4 inhibitor, is reported. Explicitly identified chiral FerroLANE ligands in the presence of rhodium catalyze the asymmetric hydrogenation of an enamine to yield sitagliptin with excellent enantioselectivity (98% ee). The process was scaled up to 5 g and the final product was isolated as a phosphate salt with >99% ee.
Keywords: asymmetric hydrogenation; catalysis; FerroLANE ligands; Rhodium; sitagliptin